2020
DOI: 10.1007/s42452-020-03665-3
|View full text |Cite
|
Sign up to set email alerts
|

Properties of fly ash geopolymer modified with red mud and silica fume: a comparative study

Abstract: Alkali-activated geopolymer has emerged as a sustainable alternative to highly polluting conventional cement. The present paper investigates the activation of fly ash-based geopolymer paste modified by red mud and silica fume. Three geopolymer mixes are considered: (1) fly ash; (2) fly ash-red mud; and (3) fly ash-silica fume. Mass proportions of modifiers in the respected mixes varied by 0, 5%, 10%, 15%, 20%, and 25% of total binder. Heat curing (60 °C) provided for 24 h just after casting. Alkaline activator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Every 5% red mud increase corresponds to a 17% decrease in flow diameter (Eq. 2) [14]. These results are not surprising because red mud has a high percentage of LOI.…”
Section: Workability Of Red Mud Based Geopolymersmentioning
confidence: 77%
See 3 more Smart Citations
“…Every 5% red mud increase corresponds to a 17% decrease in flow diameter (Eq. 2) [14]. These results are not surprising because red mud has a high percentage of LOI.…”
Section: Workability Of Red Mud Based Geopolymersmentioning
confidence: 77%
“…Ten different sample compositions are categorized as low calcium RM collected from the literature [7,[10][11][12][13][14][15][16][17][18]. From a statistical point of view, the average can be taken as the mean or median value depending on the existence of outliers [19].…”
Section: Chemical Composition Of Red Mudmentioning
confidence: 99%
See 2 more Smart Citations
“…The TCLP test and the comprehensive test show that more than 99.6% of heavy metals in geopolymer could be immobilized when the geopolymer precursor exceeds 60%. Bajpai et al, [64] did a comparative study by investigating the activation of fly ash-base geopolymer paste modified by red mud and silica fumes. The results revealed that the water absorption of fly ash geopolymer increase with red mud.…”
Section: Recent Studies On the Treatment Of Municipal Solid Waste Inc...mentioning
confidence: 99%